Sistem Pengupahan Karyawan di Salon Salma Spa Muslimah Purwokerto - Restina Musfirotun; Safitri Mukarromah (Proceedings Series on Social Sciences & Humanities, 2022)
The purpose of this research is to find out how the remuneration system at Salon Salma Spa Muslimah Purwokerto and the view of Islamic law at Salon Salma Spa Muslimah Purwokerto. The method used in this research is a qualitative method. This type of research is included in the type of field research and the nature of the research is descriptive. The data collection technique is direct interviews with business owners or owners and employees at the Salma Spa Muslimah Purwokerto salon with researchers, then the results are analyzed by editing and systematic. Based on the results of the study, it shows that the salary system for employees at Salma Spa Muslimah Purwokerto uses a percentage or income, and can be called a wholesale system. Based on the opinion of the four schools of thought, the salary system at the Salma Spa Muslimah Purwokerto salon is in accordance with Islamic law. Fulfill the pillars and conditions of ijarah and the principles of wages. Because at Salon Salma Spa Muslimah Purwokerto, it is very important to prioritize the sharia system, open to each other, transparently, fairly, and properly. However, in terms of salary/wages, Salma Spa Muslimah Purwokerto is still below the UMP/UMK.